The role of political connections on family firms' performance: Evidence from Indonesia - Iman Harymawan; Mohammad Nasih; Muhammad Madyan; Diarany Sucahyati (International Journal of Financial Studies, 2019)
The purpose of this study is to investigate the relationship of firms with family ownership and their performance in Indonesia and further examine on how political connections affect this relationship. This study used 933 samples from 413 companies listed on the Indonesia Stock Exchange (IDX) in the period between 2014 and 2016. Using ordinary least square (OLS) regression, the results shows that firms without family ownership (non-family firms) have better performance than firms with family ownership (family firms) in Indonesia. Furthermore, the findings also show that the performance of family firms significantly improve when the firms are affiliated with political connections. Our findings imply that establishing political connections in family firms will increase the performance of the firms.
Keywords: G32; G34; 330; emerging countries; family firms; firm performance; political connections